Genome elimination from the germline cells in diploid and triploid male water frogs Pelophylax esculentus - Chmielewska, Magdalena; Kaźmierczak, Mikołaj; Rozenblut-Kościsty, Beata; Kolenda, Krzysztof; Dudzik, Anna; Dedukh, Dmitrij; Ogielska, Maria (Frontiers in Cell and Developmental Biology, 2022)
Hybridogenesis is a hemiclonal reproductive strategy in diploid and triploid hybrids. Our study model is a frog P. esculentus (diploid RL and triploids RLL and RRL), a natural hybrid between P. lessonae (LL) and P. ridibundus (RR). Hybridogenesis relies on elimination of one genome (L or R) from gonocytes (G) in tadpole gonads during prespermatogenesis, but not from spermatogonial stem cells (SSCs) in adults. Here we provide the first comprehensive study of testis morphology combined with chromosome composition in the full spectrum of spermatogenic cells. Using genomic in situ hybridization (GISH) and FISH we determined genomes in metaphase plates and interphase nuclei in Gs and SSCs. We traced genomic composition of SSCs, spermatocytes and spermatozoa in individual adult males that were crossed with females of the parental species and gave progeny. Degenerating gonocytes (24-39%) and SSCs (18-20%) led to partial sterility of juvenile and adult gonads. We conclude that elimination and endoreplication not properly completed during prespermatogenesis may be halted when gonocytes become dormant. After resumption of mitotic divisions by SSCs, these 20% of cells with successful genome elimination and endoreplication continue spermatogenesis, while in about 80% spermatogenesis is deficient. Majority of abnormal cells are eliminated by cell death, however some of them give rise to aneuploid spermatocytes and spermatozoa which shows that hybridogenesis is a wasteful process.